Stability of A Sincov Type Functional Equation - Sahoo, Prasanna K. (Journal of Informatics and Mathematical Sciences, 2009)
This paper aims to study the Hyers-Ulam stability of a Sincov type functional equation $f(x,y) + f(y, z) + f(x, z) = \ell (x+y+z)$ when the domain of the functions is an abelian group and the range is a Banach space.